Adsorption and self-assembly of a mono-cyano Zn-tetraphenylporphyrin derivative on KBr(001) and MgO(001) - Ammon, Maximilian Michael; Devarajulu, Mirunalini; LIU, YI; Gurrath, Martin; Lungerich, Dominik; Jux, Norbert; Meyer, Bernd; Maier, Sabine (Surface Science, 2022)
The adsorption and self-assembly of a Zn-tetraphenylporphyrin derivative (Zn-pCNTPP) with a cyano group was investigated on KBr(001) and MgO(001) using low-temperature non-contact atomic force microscopy (nc-AFM) combined with dispersion-corrected density-functional theory (DFT). The deposition of Zn-pCNTPP at submonolayer coverage leads on both surfaces to self-assembled networks, in which the porphyrin assumes a planar adsorption configuration with the macrocycle parallel to the surface. DFT calculations confirm the planar adsorption geometry and reveal important differences in the adsorption on KBr vs. MgO. While a global minimum structure is found on KBr due to a strong CN⋯K interaction, multiple and energetically nearly equivalent adsorption sites occur on MgO. Therefore, commensurate adsorption on KBr is suggested, while optimizing the molecule–molecule over molecule–surface interactions is more important on MgO, which is experimentally both evidenced by the nc-AFM data. The expected Zn adsorption site ontop of the anion is the energetically most favored configuration only on KBr, while on MgO, it is above the surface cation.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Adsorption geometry; Dispersion-corrected density-functional theory; Molecular self-assembly; Non-contact atomic force microscopy; Porphyrins

Adsorption Behavior of a Cyano-Functionalized Porphyrin on Cu(111) and Ag(111): From Molecular Wires to Ordered Supramolecular Two-Dimensional Aggregates - Lepper, Michael; Schmitt, Tobias; Gurrath, Martin; Raschmann, Marco; Zhang, Liang; Stark, Michael Werner; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Schneider, M. Alexander; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physical Chemistry C, 2017)
We investigate the impact of peripheral cyano functionalization of the previously well-studied 2H-tetraphenylporphyrin (2HTPP) by scanning tunneling microscopy (STM) and density functional theory (DFT). The adsorption behavior of 2H-tetralds(p-cyano)-phenylporphyrin (2HTCNPP) is studied at room temperature and at 80 K on Cu(111) and Ag(111). Interestingly, the cyano-functionalized porphyrins tend to form isolated ID chains on Cu(111), in particular after mild annealing at 350 K. The individual 2HTCNPPs as well as the formed chains are oriented along the main crystallographic directions of the Cu(111) substrate due to a strongly attractive and site-specific interaction between the iminic nitrogens of the 2HTCNPP and Cu substrate atoms. The linking within the 1D molecular chains is realized by Cu adatoms as evidenced by comparison of STM and DFT. In contrast, on Ag(111) the molecules assemble into 2D supramolecular layers with long-range order and a square unit cell, stabilized by molecule-molecule interactions. The orientation of the molecules with respect to the unit cell lattice vectors leads to organizational chirality. By codeposition of cobalt, the porphyrin molecules are metalated at room temperature. We did not observe any evidence for metal-organic network formation on Ag(111), even after varying the deposition parameters or the order of metal and porphyrin deposition. Our study shows that cyano functionalization of porphyrins can give rise to novel and unique self-assembled structures like 1D molecular chains without any cross-connections via adatom linking.

Adsorption energies of porphyrins on MgO(100): An experimental benchmark for dispersion-corrected density-functional theory - Wolfram, Alexander; Tariq, Quratulain; Fernández, Cynthia C.; Muth, Maximilian; Gurrath, Martin; Wechsler, Daniel; Franke, Matthias; Williams, Federico J.; Steinrück, Hans-Peter; Meyer, Bernd; Lytken, Ole (Surface Science, 2022)
Using temperature-programmed desorption, adsorption energies of metallotetraphenylporphyrins were measured and used as a benchmark for dispersion-corrected density-functional theory calculations. Experimentally, simple Redhead analysis was used to extract monolayer adsorption energies for cobalt, zinc and magnesium 5,10,15,20-tetraphenyl porphyrin on MgO(100) thin films grown on Ag(100), where the prefactor for desorption was calculated by transition-state theory. Magnesium exhibits the highest experimental adsorption energy of 217 kJ/mol, while zinc and cobalt have adsorption energies of 193 and 186 kJ/mol, respectively. Using density-functional theory with a modified Grimme D3 scheme resulted in calculated adsorption energies of 209, 171 and 174 kJ/mol. The trend and even the absolute values of the experiment and the theory are in good agreement. Additionally, the calculations allow us to break down the different contributions to the adsorption energies, showing the interplay of van der Waals interactions, chemical bonds and deformation energies.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Adsorption energies; Dispersion-corrected density-functional theory; MgO(100); Porphyrins; Temperature-programmed desorption

Binary supramolecular networks of bridged triphenylamines with different substituents and identical scaffolds - Steiner, Christian; Yang, Zechao; Gliemann, Bettina; Meinhardt, Ute; Gurrath, Martin; Ammon, Maximilian Michael; Meyer, Bernd; Kivala, Milan; Maier, Sabine (Chemical Communications, 2018)
Based on scanning tunneling microscopy experiments combined with density functional theory, we report the formation and the electronic structure of porous binary supramolecular networks on Au(111). The two triphenylamine derivatives with identical scaffolds intermix due to a maximization of the overall number of H-bonds instead of an optimization of the H-bond strength in the bonding motif. The HOMO-LUMO gap is defined by both molecules, which is typical for electron donor-acceptor networks.

Formation of highly ordered molecular porous 2D networks from cyano-functionalized porphyrins on Cu(111) - Steinrück, Hans-Peter; Adhikari, Rajan; Siglreithmaier, Gretel; Gurrath, Martin; Meusel, Manuel; Kuliga, Jan; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Marbach, Hubertus (Chemistry - A European Journal, 2020)
We investigated the adsorption of three related cyano-functionalized tetraphenyl porphyrin derivatives on Cu(111) by scanning tunneling microscopy (STM) in ultra-high vacuum (UHV) with the goal to identify the role of the cyano group and the central Cu atom for the intermolecular and supramolecular arrangement. The porphyrin derivatives studied were Cu-TCNPP, Cu-cisDCNPP, and 2H-cisDCNPP, that is, Cu-5,10,15,20-tetrakis-(p-cyano)-phenyl-porphyrin, Cu-meso-cis-di(p-cyano)-phenyl-porphyrin and 2H-meso-cis-di(p-cyano)-phenyl-porphyrin, respectively. Starting from different structures obtained after deposition at room temperature, all three molecules form the same long-range ordered hexagonal honeycomb-type structure with triangular pores and three molecules per unit cell. For the metal-free 2H-cisDCNPP, this occurs only after self-metalation upon heating. The structure-forming elements are pores with a distance of 3.1 nm, formed by triangles of porphyrins fused together by cyano-Cu-cyano interactions with Cu adatoms. This finding leads us to suggest that two cyano-phenyl groups in the "cis" position is the minimum prerequisite to form a highly ordered 2D porous molecular pattern. The experimental findings are supported by detailed density functional theory calculations to analyze the driving forces that lead to the formation of the porous hexagonal honeycomb-type structure.
CRIS-Team Scopus Importer:2020-07-03
Keywords: porphyrins coordinated networks cyano functionalization scanning tunneling microscopy (STM) density-functional theory (DFT) calculations

"Inverted'' porphyrins: a distorted adsorption geometry of free-base porphyrins on Cu(111) - Lepper, Michael; Köbl, Julia; Schmitt, Tobias; Gurrath, Martin; De Siervo, Abner; Schneider, M. Alexander; Steinrück, Hans-Peter; Meyer, Bernd; Marbach, Hubertus; Hieringer, Wolfgang (Chemical Communications, 2017)
Based on density functional theory calculations combined with experimental results, we report and discuss an extremely distorted, "inverted'' adsorption geometry of free-base tetraphenylporphyrin on Cu(111). The current findings yield new insights into a wellstudied system, shedding light on the peculiar molecule-substrate interaction and the resulting intramolecular conformation.

Is the polarity of the Co3O4(111) surface compensated by electron transfer from bulk donor defects? - Gurrath, Martin; Schlott, Hannah; Meyer, Bernd (Surface Science, 2023)
Experimental studies have shown that the Co3O4(111) surface exists as an unreconstructed (1 × 1) truncated bulk termination. Polarity compensation of this polar surface thus has to occur by a transfer of electrons, which creates partially occupied valence states and makes the surface metallic. Here we show by Hubbard-U corrected density-functional theory calculations that such a polarity compensation mechanism would make the surface highly reactive, which is not in agreement with experimental observations. An additional compensation mechanism has to be at work, by which the partially occupied valence band states are filled by electrons without requiring a reconstruction of the surface. As such an mechanism we propose the transfer of electrons from bulk donor defects to the surface. By employing this mechanism in our calculations we recover the experimentally observed reactivity. This demonstrates that for all polar surfaces, which are fully or partially polarity compensated by the transfer of electrons, additional electronic effects have to be considered in any electronic structure calculation in order to capture the correct surface chemistry.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Charge neutralization; Cobalt oxide; Density-functional theory; Polar surfaces

Porphyrin Metalation at MgO Surfaces: A Spectroscopic and Quantum Mechanical Study on Complementary Model Systems - Schneider, Johannes; Franke, Matthias; Gurrath, Martin; Röckert, Michael; Berger, Thomas; Bernardi, Johannes; Meyer, Bernd; Steinrück, Hans-Peter; Lytken, Ole; Diwald, Oliver (Chemistry - A European Journal, 2016)
We show that both single-crystalline and nanostructured MgO surfaces convert free-base tetraphenyl porphyrin (2HTPP) into magnesium tetraphenyl porphyrin (MgTPP) at room temperature. The reaction can be viewed as an ion exchange between the two aminic protons of the 2HTPP molecule with a Mg ion from the surface. The driving force for the reaction is the strong stability of the formed hydroxyl groups along the steps and at defects on the MgO surface. We have used an integrated characterization approach that includes UV/Vis diffuse reflectance measurements on nanostructured powders, X-ray photoelectron spectroscopic investigation of atomically clean MgO(100) single-crystalline thin films, and density functional theory (DFT) calculations on model systems. The DFT calculations demonstrate that MgTPP formation is strongly exothermic at the corners, edges and steps, but slightly endothermic on terrace sites. This agrees well with the UV/Vis diffuse reflectance, which upon adsorption of 2HTPP shows a decrease in the absorption band associated with corner and edge sites on MgO nanocube powders. Porphyrin swap shop: Spectroscopic adsorption studies on two complementary model systems, atomically clean thin MgO(100) films and MgO nanocube powders, show that low-coordinated surface cations located in corner, edge, or step regions of the MgO surfaces are subject to ion exchange between adsorbed porphyrin molecules and the oxide surface.
Keywords: ion exchange; metalation; nanocubes; porphyrin; surface defects

Self-Assembly and Stability of Hydrogen-Bonded Networks of Bridged Triphenylamines on Au(111) and Cu(111) - Steiner, Christian; Gliemann, Bettina; Meinhardt, Ute; Gurrath, Martin; Meyer, Bernd; Kivala, Milan; Maier, Sabine (Journal of Physical Chemistry C, 2015)
The adsorption, chemical nature, and self-assembly of diaminotriazinyl- and carboxyl-substituted triphenylamines with dimethylmethylene bridges were studied on Au(111) and Cu(111) at submonolayer coverage by low-temperature scanning tunneling microscopy and density functional theory. On Au(111), both molecules form extended porous honeycomb networks. The geometry of the networks agrees well with density functional theory optimized hydrogen-bonded gas phase structures. Therefore, the self-assemblies on Au(111) are strongly directed by intermolecular hydrogen bond interactions. In contrast, on Cu(111) both molecules aggregate in dense islands owing to the stronger moleculesurface interaction. While the carboxyl substituents partially deprotonate at room temperature on Cu(111), the diaminotriazinyl-substituted triphenylamines adsorb mainly intact. The diaminotriazinyl groups deprotonate gradually at increased adsorption temperatures.